A Study Method of Elementary School Teachers Training in Teacher Training Center - A. Farahani; A. Nasr-E-Esfahani; M. sharif Khalif Soltani (Fanāvarī-i āmūzish, 2010)
Considering that teacher is important and the most important factors in the development of effect qualitative education system, the present research have assessed methods of elementary school teacher’s training. In this research, the quantitative and quality methods of study have been utilized. The statistical population of this research includes the principals of elementary schools, experts, and teachers of teacher training center of Qom in the educational year of 2008-2009.  In order to select the principals, classified sampling method was used in congruency with the size; purposeful sampling method was used to determine the experts' sample. In this regard 162 principals', 20 experts and members of the faculty's view analyzed who had a great research background. The validity of the questionnaire and the interview has been confirmed by some of the professors and PhD and M.A students. The reliability of the questionnaire has been estimated in selection as 0.87 respectively, using the Crunbach alpha. In order to analyze the results descriptively and analytically, the SPSS software has been used; in order to analyze the interview, the categorization method has been utilized. The results show that In order to teach and train the teachers, up- to- date and implicational subjects and courses should be prepared, experienced and qualified teachers should be employed, training courses should be held, equipments should be provided in accordance with the teachers' needs to improve the generic and technical qualification of both students and teachers. In this regard, using the experience of developed countries (Paying attention to cultural differences); in teacher training programs were underlined to make the reviewing, amending and developing possible. Finally, some recommendations were suggested to improve the training of the elementary teachers.